Drivers of virtual water flows on regional water scarcity in China. (10th January 2019) - Cai, Beiming; Zhang, Wei; Hubacek, Klaus; Feng, Kuishuang; Li, ZhenLiang; Liu, Yawen; Liu, Yu
Abstract: Previous studies had shown that the virtual water flows had intensified local water scarcity of China. There is an urgent need to identify the drivers of virtual water flows and provide the potential options to reduce the impact of virtual water flows on regional water scarcity. Based on the multi-regional input-output model and structural decomposition analysis, we evaluated the redistribution of water withdrawal within China in 2002, 2007 and 2012, and then revealed the hidden driving forces of the changes in virtual water flows. For a specific province, the drivers had been divided into local and the rest of China. Here we found that: (1) The share of virtual water flows in interregional trade to total water withdrawal had increased (from 20.1% to 40.5%) during the study period. (2) The direction of virtual water flows has reversed between some Chinese regions. Northwest and Northeast regions have become the major virtual water exporters. (3) The virtual water flows hidden in traded products of agriculture, electricity and the chemical industry accounted for more than 83% of total virtual water flows. (4) Local efficiency gains and consumption pattern changes in other provinces were the main drivers for changes in virtual water flows. The water-scarce Northwest and Northeast of China had further increased virtual water export to the water-rich provinces in southern China. This trend could be curbed by improving water use efficiency and restraining water-intensive consumption. Our results could pinpoint areas to invest in water use efficiency and provide guidance for areas to restrain water-intensive consumption. Highlights: The study evaluated interprovincial virtual water flows in China during 2002–2012. The main drivers for the changes in virtual water flows have been analyzed. Virtual water flows play an increasingly role in water use of China. The direction of virtual water flows has changed from 2002 to 2012. Water use efficiency and consumption pattern were the major drivers.